Melhorando o desempenho da técnica de clusterização hierárquica single linkage utilizando a metaheurística GRASP - Ribeiro Filho, Napoleão Póvoa (Universidade Federal do Tocantins, 2018)
The problem of clustering (grouping) consists of, from a database, group the elements so that more queries are in the same cluster (group) and less similar elements are different clusters. There are several ways to accomplish these groupings. One of the most popular is the hierarchical, where a hierarchical relationships between the elements is created. There are several methods of analyzing the similarity between elements in the clustering problem. The most common among them is the single linkage method, which brings together the elements that are experiencing less apart. To apply the technique in question, distance matrix is the input used. This grouping process generates the end an inverted tree known as dendrogram. The cophenetic correlation coefficient (ccc), obtained after the construction of the dendrogram is a measure used to evaluate the consistency of the clusters generated and indicates how faithful he is in relation to the original data. Thus, a dendrogram gives more consistent clusters when the ccc is closer to one (1). The clustering problem in all its aspects, including hierarchical clustering (object of study in this work), belongs to the class of NP-complete problems. Therefore, it is common to use heuristics for efficient solutions to this problem. In order to generate dendrograms that result in better ccc, it is proposed in this paper a new algorithm that uses the concepts of GRASP metaheuristic. It is also objective of this work to implement such a solution in parallel computing in a computer cluster, thus working with arrays larger. Tests were conducted to confirm the performance of the proposed algorithm, comparing the results with those generated by the software R.